Fiscal Convergence in an Enlarged European Union - Georgeta VINTILĂ; Mihaela ONOFREI; Ioana Laura ŢIBULCĂ (Transylvanian Review of Administrative Sciences, 2014)
Taxation convergence in the European Union has always been a heatedly debated issue, and it has constantly resurfaced to the limelight as more and more fiscal directive proposals are being discussed. The current study is an analysis of the evolution of taxation convergence tendencies within the European Union in recent years, using sigma-convergence and cluster analysis. Our goal is to analyze the fiscal convergence trends in the context of European Union enlargement over the last two decades.